The New Understanding of Sculptors’ Self in Early Medieval Italy and Northern Europe - Gordusenko, Maria I. (Actual Problems of Theory and History of Art, 2023)
The phenomena of medieval artists’ identity and self-representation remain among the most complex, intriguing and promising topics for research. This paper challenges the stereotype of an anonymous medieval artist and offers a new view of artistic self-reference in the Middle Ages. The case is made through analysis of a series of three-dimensional examples, which have not received sufficient attention in previous scholarship. Produced by sculptors, bronze casters and goldsmiths active in the territories of present-day Italy and Germany, I consider the case studies with self-representation as signs of devotion and self-awareness of their makers. Most of the self-representations discussed in this thesis are identifiable either through inscriptions, ‘signatures,’ or on the basis of documentary evidence. A select number of these examples serve as main case studies in this paper. By analysing a number of artists’ self-representations, this paper offers an alternative view on lives and work of early mediaeval sculptors and suggests overcoming the stereotype of the anonymous artist in the Middle Ages. At the same time, this paper cautiously avoids projecting another stereotypical misconception, namely a post-medieval view of an artist as an intellectual individual gifted with outstanding creativity. Notably, self-representations that are subjects of research in this paper are integrated within works of art produced for use in Christian practice, devotion and ceremonial. The case studies produced in the territories of Italia and Germania are not presented as isolated from other pieces with artists’ self-representations created in various media and in different European regions.